2004
DOI: 10.1074/jbc.m403412200
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Essential Core of a Cysteine-based Protein-tyrosine Phosphatase Revealed by a Novel 16-kDa VH1-like Phosphatase, VHZ

Abstract: The smallest active protein-tyrosine phosphatase yet (only 16 kDa) is described here and given the name VHZ for VH1-like member Z because it belongs to the group of small Vaccinia virus VH1-related dual specific phosphatases exemplified by VHR, VHX, and VHY. Human VHZ is remarkably well conserved through evolution as it has species orthologs in frogs, fish, fly, and Archaea. The gene for VHZ, which we designate as DUSP25, is located on human chromosome 1q23.1 and consists of only two coding exons. VHZ is broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 36 publications
6
35
1
Order By: Relevance
“…It appears likely that the handful of archaeal PPMs were acquired "secondhand" from the Bacteria. The widespread phylogenetic dispersal of the cPTPs and LMW PTPs is indicative of ancient origins that likely date back to the last universal common ancestor (33)(34)(35). Although rhodanese, the progenitor of the Cdc25 dual-specificity protein phosphatases, is pervasive among prokaryotic organisms, Cdc25 appears to be exclusively eukaryal in residence and, by extension, origin (24).…”
Section: Whence Eukaryotic Protein Kinases and Phosphatases?mentioning
confidence: 99%
“…It appears likely that the handful of archaeal PPMs were acquired "secondhand" from the Bacteria. The widespread phylogenetic dispersal of the cPTPs and LMW PTPs is indicative of ancient origins that likely date back to the last universal common ancestor (33)(34)(35). Although rhodanese, the progenitor of the Cdc25 dual-specificity protein phosphatases, is pervasive among prokaryotic organisms, Cdc25 appears to be exclusively eukaryal in residence and, by extension, origin (24).…”
Section: Whence Eukaryotic Protein Kinases and Phosphatases?mentioning
confidence: 99%
“…Thus, the minimal DSP core (aa 28 -171) of VH1 is only minimally active in the absence of its DD. This is in stark contrast to other VH1-like phosphatases like VHZ (also known as DUSP25), for which the minimal ϳ16 kDa DSP core carries all structural and functional determinants sufficient for catalytic activity (33). As a corollary, the minimal sets of secondary structural elements conserved in all knownVH1-like DSPs (5 ␣-helices and 5 ␤-strands) as well as the presence of a catalytic triad (Cys/Arg/ Asp) are not sufficient requirements for a catalytically active DSP core.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, the inhibitors found in this study seem to be capable of establishing strong multiple hydrogen bonds in the active site of VHZ. Benzoate, benzene-1,2-diol, 5-imino-5,6-dihydro- [1,3,4]thiadiazolo[3,2-a]pyrimidin-7-one, [1,2,4] triazolo [3,4-b] [1,3,4]thiadiazole, nitrobenzene, and 2-hydroxybenzoate moieties in 1, 2 and 5, 3, 4, 6, and 7 are respectively expected to serve as an effective surrogate for the phosphotyrosine group in substrates of VHZ. To the best of our knowledge, compounds 1-7 have not been reported as a phosphatase inhibitor so far, and no additional biological activity was found at least in the two most public chemical databases, ChEMBL and PubChem.…”
Section: Resultsmentioning
confidence: 99%
“…1 VHZ is one of the smallest phosphatases with 150 amino acids and contains the minimal set of secondary structure elements conserved in all known phosphatases. 2 Recently, it was demonstrated that the activation and the knockdown of VHZ would, respectively, have an effect of enhancing and retarding the progression of the cell cycle associated with carcinogenesis from the G1 to S phase. 3 Furthermore, VHZ was shown to be overexpressed in multiple human primary cancers, including breast cancer.…”
Section: Introductionmentioning
confidence: 99%